REVITALISASI MANAJEMEN KURIKULUM ERA 5.0 - Mutammimah, Hafidhotul; Nahdliyah, Amirotun (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
Abstract: This study aims to examine the transformation of teachers' roles, school collaboration with the industrial world, and the implementation of project-based curriculum in responding to educational challenges in the 5.0 era. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews with teachers and students, direct observation of learning activities, and documentation of the implementation of collaboration and project-based learning programs at MTsN 8 Banyuwangi. Data were analyzed using the Milles and Huberman interactive model, which includes data reduction, data presentation in descriptive narratives, and drawing conclusions. The results of the study indicate that the transformation of teachers' roles from teachers to technology-based learning facilitators is able to support students in learning independently and creatively, despite challenges such as limited access to technology. School collaboration with the industrial world provides direct experience that strengthens students' entrepreneurial and digital literacy skills, increasing their self-confidence, creativity, and innovation abilities. Meanwhile, the implementation of a project-based curriculum has proven effective in developing students' critical thinking, problem-solving, and collaboration skills, supported by the theories of Experiential Learning and Constructivism. Overall, this study concludes that all three approaches are successful in creating learning that is relevant to the needs of the 21st century, although further efforts are needed to overcome technical constraints and maximize learning potential.